The IMPLEMENTATION OF SEO USING ON-PAGE AND OFF-PAGE METHODS TO INCREASE BRAND AWARENESS : CASE STUDY IN THE ARTICLE VOCASIA BLOG - Sinaga, Jhonatan; Dharmanto, Agus; Franciscus Dwikotjo Sri Sumantyo (Draf Solusi Indonesia, 2023)
This study aims to determine whether the implementation of On-Page and Off-Page SEO partially and simultaneously affects Brand Awareness. This type of research is quantitative. The technique used is purposive sampling using the Slovin formula, where the number of samples is 100 respondents. Collecting data using a questionnaire through the Validity and Reliability test. The data analysis technique used was multiple linear regression analysis. The results showed that the OnPage SEO and Off-Page SEO variables partially and simultaneously had a positive and significant effect on Brand Awareness.